2015
DOI: 10.1177/1077801215597790
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Sexual Assault–Specific Prosocial Bystander Behavior and Intentions

Abstract: This study prospectively examined the impact of men's own attitudes and behaviors and perceptions of peer attitudes and behaviors on intentions and engagement in prosocial bystander behavior. Undergraduate men completed surveys at baseline and 4-and 7-month follow-ups. Men's perceptions of peer attitudes and behaviors and their own attitudes and behaviors were both important predictors of intentions. However, men's own attitudes and behaviors appeared to be more robustly predictive of behavior. Intentions to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…The broader preponderance of evidence, mostly among adult populations and largely at the community level, suggest that negative gender norms, especially related to accepting norms supporting violence against women, are associated with higher levels of both physical and sexual violence against women [2527]. Furthermore, many sexual and physical violence prevention programs, especially those aimed at men, include a norms-changing component aimed at supporting pro-social behavior, and ultimately, social transformation [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…The broader preponderance of evidence, mostly among adult populations and largely at the community level, suggest that negative gender norms, especially related to accepting norms supporting violence against women, are associated with higher levels of both physical and sexual violence against women [2527]. Furthermore, many sexual and physical violence prevention programs, especially those aimed at men, include a norms-changing component aimed at supporting pro-social behavior, and ultimately, social transformation [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…In a second study, they found that higher peer norms supporting helping was related to fewer missed opportunities to intervene (Hoxmeier et al, 2020). Murphy Austin and colleagues (2016) found that while perceptions of peer helping norms somewhat predicted actual helping behavior, the individual’s own beliefs and attitudes more robustly predicted helping than peer norms. Peer helping norms are clearly influencing some aspects of helping behavior; however, the inconsistent nature of the relationship warrants a closer consideration.…”
Section: Introductionmentioning
confidence: 93%
“…The findings on peer norms’ influence on actual helping behaviors in SV contexts specifically are mixed (Austin, Dardis, Wilson, Gidycz, & Berkowitz, 2016; Banyard & Moynihan, 2011; Brown et al, 2014; Hoxmeier, Acock, & Flay, 2020; Hoxmeier, Flay, & Acock, 2018). Banyard and Moynihan (2011) found that perceptions of higher peer norms supporting coercion were, surprisingly, related to greater actual helping behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…A number of evaluations of bystander programming efforts related to sexual violence measure the willingness to intervene, or behavioral intent, as an outcome, whereas fewer studies measure the impact of programs on an individual's self-reported bystander behavior. However, relying on measurement of behavioral intent as proxy for behavior is not sufficient in the field of sexual violence (Murphy Austin, Dardis, Wilson, Gidycz, & Berkowitz, 2016). An individual's willingness to intervene does not necessarily mean the person intervenes, due to a number of factors, such as not knowing what to do or fear of making the situation worse (Burn, 2009;Bennett, Banyard & Garnhart, 2013;McMahon & Dick, 2011).…”
mentioning
confidence: 99%